1995
DOI: 10.1016/s0266-7681(05)80026-9
|View full text |Cite
|
Sign up to set email alerts
|

Radial Instability of the Metacarpophalangeal Joint of the Thumb

Abstract: Human cadaver thumbs were tested to evaluate stability of the radial side of the MP joint. The contributions of the dorsal capsule, radial collateral ligament, accessory collateral ligament, and volar plate were examined with the joint in 0 degrees and 30 degrees of flexion. At 0 degrees flexion, the average joint angulation increased 4 degrees following isolated radial collateral ligament transection and 6 degrees following isolated accessory collateral ligament transection. Release of both the accessory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…7 Both the RCL and UCL contribute to dorsal support as well as to lateral stability. 7,8 The RCL originates dorsally on the lateral condyle of the metacarpal head and extends in a distal and palmar direction to insert into the lateral tubercle of the proximal phalanx. The main stabilizer laterally is the proper ligament, which runs from the dorsally situated metacarpal condyle and inserts obliquely and volarly to the proximal third of the proximal phalanx, merging with the accessory collateral ligament (Fig.…”
Section: Anatomy and Physiologymentioning
confidence: 99%
“…7 Both the RCL and UCL contribute to dorsal support as well as to lateral stability. 7,8 The RCL originates dorsally on the lateral condyle of the metacarpal head and extends in a distal and palmar direction to insert into the lateral tubercle of the proximal phalanx. The main stabilizer laterally is the proper ligament, which runs from the dorsally situated metacarpal condyle and inserts obliquely and volarly to the proximal third of the proximal phalanx, merging with the accessory collateral ligament (Fig.…”
Section: Anatomy and Physiologymentioning
confidence: 99%
“…Loebig et al demonstrated sequential laxity that resulted from serial dividing of radial structures at the thumb MCP joint. 2 After RCL dividing, they found only a 4 difference in laxity at 0 of flexion, and a 5 difference at 30 . They commented that this difference would neither be clinically detectable nor disabling.…”
Section: Discussionmentioning
confidence: 97%
“…This value has previously been cited as the approximate force applied during stress examination by a surgeon. 2 The radial instability of the joint was measured using a goniometer in 15 increments of MCP flexion from 0 to full flexion. The RCL was then detached from the proximal phalanx by dividing the ligamentous structures dorsal to the volar plate.…”
Section: Methodsmentioning
confidence: 99%
“…The anatomy and biomechanics of the MCP joint as it pertains to these injuries is very well described in the literature. 2,3,6,7,11,12,14,16,21,23,25,29 Although there are a large variety of options for reconstruction of the UCL, there is also evidence to suggest that there is no difference in outcomes after acute ligament repair versus chronic ligament reconstruction. 31 In July, 2013, Samora et al published their results of a systematic review of the literature analyzing all cohorts of thumb UCL injuries with at least 2-year follow-up in the English literature.…”
Section: Discussionmentioning
confidence: 99%